Music Teachers’ Use of Online Video Platforms (OVPs) in Lesson Design and Instruction /Uso de plataformas de video en línea (OVPs) por profesores de música en el diseño didáctico y la práctica educativa - Yooji Hwang; Beatriz Ilari (Revista Latinoamericana de Tecnología Educativa)
New technological developments and the popularity of the internet have changed the ways that people learn, listen to, make and teach music. Many music teachers now use a variety of digital tools to enhance their students’ learning in the classroom. However, the use of technology in music education, and particularly videos, is still an under-researched area. This paper reports on an exploratory investigation of music teachers’ use of online video platforms (OVP) such as YouTube, Vimeo, Panopto, and Dailymotion in lesson design and instruction. Through an online survey with 21 American music teachers, we gauged: (1) the frequency of use of videos in lesson design and teaching, (2) types of videos used by teachers, (3) the qualities of videos that teachers used, and (4) whether there were differences in video usage between grade levels and modalities of their music class. Findings suggested that music teachers frequently used OVPs both when planning and instructing their lessons, believing that such uses would make their lessons more engaging. Implications for music education are outlined at the end of the report. /// O desenvolvimento de novas tecnologias e a popularidade da internet têm transformado nossos modos de ouvir, fazer e ensinar música. Muitos professores de música fazem uso da tecnologia em suas aulas de música com o intuito de enriquecer as experiências de seus alunos. No entanto, ainda há poucos estudos sobre o uso da tecnologia na educação musical, e, sobretudo, o uso de videos. Neste artigo, discutimos os resultados de um estudo exploratório acerca do uso de plataformas digitais de video como YouTube, Vimeo, Panopto e Dailymotion, por professores de música norte-americanos e em suas aulas. Através de um survey com 21 professores, nós investigamos: (1) a frequência de uso de videos no planejamento e nas aulas de música, (2) os tipos de videos utilizados por professors, (2) as caracteristicas dos videos utilizados em aulas de música, e (4) se há diferenças no uso de videos em aulas de música por ano letivo e modalidade (orquestra, banda, coral, e musicalização). Os resultados do survey sugerem que os professores de música usam plataformas digitais de video no planejamento e nas aulas de música, acreditando que os videos tornam as aulas mais ricas e interessantes. Implicações para a educação musical são delineadas ao final do artigo.